STUDI TENTANG MINAT BERWIRAUSAHA SISWA JURUSAN KRIYA LOGAM DI SMK NEGERI 8 PADANG - YENTI MARLINA, Drs. M. Nasrul Kamal, M.Sn, Dr. Yahya, M.Pd (Serupa The Journal of Art Education, 2015)
This study aims to determine the efforts of teachers and school growinginterest in entrepreneurship to students, and knowing the interests of students majoring in Kriya Logam at SMK 8 Padang to entrepreneur. Metodologi in research is descriptive qualitative research methods. Source of data obtained from structured interviews with teachers and students in Kriya Logam department at SMK 8 Padang. The data obtained were analyzed by using the model of Miles and Huberman. The effort of teachers and schools in growing interest in entrepreneurship to students at SMK 8 Champaign include providing motivation entrepreneurship to students in any learning process is done, provide exemplary / entrepreneurship example, involve students in the production unit, held an exhibition at the end of each semester and brings students practice in metal craft industries. For student interest in entrepreneurship is seen that the class X students do not have a picture of entrepreneurship and venture what will be done, on an existing class XI student interest in entrepreneurship and in class XII students have a high interest in entrepreneurship and already have a picture of the business to bedone. Benefits of research for teachers in order to motivate students to doindependent business activities, guiding, and involve students in theproduction unit in turn.